1961
DOI: 10.58799/b-72
|View full text |Cite
|
Sign up to set email alerts
|

Mineral deposits of Luna County, New Mexico

Abstract: Luna County mines have produced $8.64 million in minerals since the first recorded mining operations in 1876. The bulk of this production has been from lead-zinc-silver ores, but appreciable amounts of manganese, fluorspar, copper, and gold also have been mined. The principal producing districts of the past were the Cooks Peak, Victorio, Tres Hermanas, Little Florida, and Fluorite Ridge. Lesser districts include the Fremont, Florida, and Cedar-Carrizalillo.Mining is now at a standstill in Luna County because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Darton (1916) notes that a small shipment of copper -rich ore with c1ssociatPd gold was made from a Vt'in in the northwestern part of the Carrizalillo Hills. Griswold (1961) provides the latest and best summary of mineral deposits in the Carrizalillo Hills. He describes chrysocolla, millachite, and azurite associated vvith quartz, ca'rbonatc, and breccia veins in the broken region northwest of Johnson Mountain, gold prospects located "just east of f fermanas and north of the highw.iy," which produced a few shipmf'nts of ore; and tlll' copper-beanng andesite at the Cillumet mine in the so11th crn Ci1rrizalillo Hills.…”
Section: Potassic Alteration and Normal Faulting Relationshipmentioning
confidence: 99%
“…Darton (1916) notes that a small shipment of copper -rich ore with c1ssociatPd gold was made from a Vt'in in the northwestern part of the Carrizalillo Hills. Griswold (1961) provides the latest and best summary of mineral deposits in the Carrizalillo Hills. He describes chrysocolla, millachite, and azurite associated vvith quartz, ca'rbonatc, and breccia veins in the broken region northwest of Johnson Mountain, gold prospects located "just east of f fermanas and north of the highw.iy," which produced a few shipmf'nts of ore; and tlll' copper-beanng andesite at the Cillumet mine in the so11th crn Ci1rrizalillo Hills.…”
Section: Potassic Alteration and Normal Faulting Relationshipmentioning
confidence: 99%
“…The Park (Hilltop) mine is locate d in the SE% sec. 35, r. 25 S., R. 8 ~V Griswold (1961) reporll'd that A. J. Mah n s taked the liilltop claim over the deposit m 1958, but most of the development had been done many years betore. Thoroughly oxidized veins in Fusselman Dolomite contain dry bone smithsonite and minor cerus~ite .…”
Section: Normal Faultsmentioning
confidence: 99%
“…Major producers were the Chance and Jessie claims; other important properties were the Rover, Rambler, Excess, and Helen claims. Ore minerals were listed by Griswold (1961) as cerussite, anglesite, silver halides, and native gold, with minor smithsonite and secondary copper minerals in a gangue of quartz, calcite, and various iron oxides. Lindgren, Graton, and Gordon (1910) observed that all the ores contained some arsenic.…”
mentioning
confidence: 99%